Revenge of the Spellmans - Lutz, Lisa (Simon & Schuster Paperbacks, 2010)
Private investigator Isabel Spellman is back on the case and back on the couch - in court-ordered therapy after getting a little too close to her previous subject. Izzy is on hiatus from Spellman, Inc. However, when her boss simultaneously cuts her bartending hours and introduces her to a "friend" looking for a private eye, Izzy reluctantly finds herself with a new client. She assures herself the case will be short and sweet. But Izzy soon has more questions than answers